Exploring Key Determinants of Trail Run Athlete’s Preparedness to Perform Pre-Hospital First Aid for Ankle Sprain - Zulkarnain, Hakim; Indhiantoro, Galih; Dewi, Yulis Setiya; Astutik, Wahyu Sri; Matos, Filomena Adelaide de (JURNAL INFO KESEHATAN, 2024)
Trail runs have a high risk of injury like ankle sprains. Proper ankle sprain first aid requires preparedness to prevent more serious danger and ensure its success in the pre-hospital setting. This study aimed to explore key determinants of trail run athletes’ preparedness to perform pre-hospital first aid for ankle sprain using the PRECEDE-PROCEED Model theory. The research method used a descriptive correlational which approached cross-sectionally. The research recruited 120 trail run athletes of two professional clubs who were selected by simple random sampling. Data was collected using questionnaires. The variables measured were knowledge, belief, value, attitude, and confidence. Bivariate analysis used chi-square and spearman-rho tests. Multivariate analysis used a logistic regression test. All of the statistical analyses used α = 0,05. The research results show that half of the respondents was 18 – 35 years old. The factors correlated to the trail run preparedness to perform pre-hospital first aid for ankle sprain was as follows. The majority had a medium level of knowledge (54,2%) and a significance level of p = 0.000. Similar trends were found between belief, value, and confidence in which there were no low levels of those variables with the same significance value of p = 0.000. Lastly, respondent’s percentages of attitudes were almost equally distributed between negative (45%) and positive (66%) with a significance level of p = 0,000. In multivariate analysis, all the variables had p-values < 0,05. The OR was as follows, knowledge 14,713; belief 77,919; value 27,554; attitude 7,213; and confidence 12,408.  The conclusion is found that knowledge, belief, value, attitude, and confidence were significantly correlated with the athlete’s preparedness Together all variables were correlated significantly to the athlete’s preparedness to perform pre-hospital first aid for ankle sprain. In conclusion, to improve athlete safety during trail runs is by improving the preparedness for any adverse event including trail runs. All of the factors could increase preparedness, but some factors resulted in higher preparedness. The factors that have more effect on preparedness than the others are belief and value.